Monitoring of Sierra Nevada Caves Reveals the Potential for Stalagmites to Archive Seasonal Variability - Wortham, Barbara E.; Montañez, Isabel P.; Bowman, Kimberly; Kuta, Daphne; Contreras, Nora Soto; Brummage, Eleana; Pang, Allison; Tinsley, John; Roemer-Baer, Greg (Frontiers in Earth Science, 2021)
In the southwestern United States, California (CA) is one of the most climatically sensitive regions given its low (≤250 mm/year) seasonal precipitation and its inherently variable hydroclimate, subject to large magnitude modulation. To reconstruct past climate change in CA, cave calcite deposits (stalagmites) have been utilized as an archive for environmentally sensitive proxies, such as stable isotope compositions (δ18O, δ13C) and trace element concentrations (e.g., Mg, Ba, Sr). Monitoring the cave and associated surface environments, the chemical evolution of cave drip-water, the calcite precipitated from the drip-water, and the response of these systems to seasonal variability in precipitation and temperature is imperative for interpreting stalagmite proxies. Here we present monitored drip-water and physical parameters at Lilburn Cave, Sequoia Kings Canyon National Park (Southern Sierra Nevada), CA, and measured trace element concentrations (Mg, Sr, Ba, Cu, Fe, Mn) and stable isotopic compositions (δ18O, δ2H) of drip-water and for calcite (δ18O) precipitated on glass substrates over a two-year period (November 2018 to February 2021) to better understand how chemical variability at this site is influenced by local and regional precipitation and temperature variability. Despite large variability in surface temperatures and precipitation amount and source region (North Pacific vs. subtropical Pacific), Lilburn Cave exhibits a constant cave environment year-round. At two of the three sites within the cave, drip-water δ18O and δ2H are influenced seasonally by evaporative enrichment. At a third collection site in the cave, the drip-water δ18O responds solely to precipitation δ18O variability. The Mg/Ca, Ba/Ca, and Sr/Ca ratios are seasonally responsive to prior calcite precipitation at all sites but minimally to water-rock interaction. Lastly, we examine the potential of trace metals (e.g., Mn2+ and Cu2+as a geochemical proxy of recharge and find that variability in their concentrations has high potential to denote the onset of the rainy season in the study region. The drip-water composition is recorded in the calcite, demonstrating that stalagmites from Lilburn Cave, and potentially more regionally, could record seasonal variability in weather even during periods of substantially reduced rainfall.